Abundance, species richness and diversity of forest bird assemblages – The relative importance of habitat structures and landscape context. (December 2021) - Basile, Marco; Storch, Ilse; Mikusiński, Grzegorz
Highlights: Diameter of living and standing dead trees, and deadwood drive forest bird abundance. The landscape context influences bird numbers in structurally similar forests. Broadleaf cover and distance between forest sites drive bird richness and diversity. Simply providing habitat structures for conservation is not a viable solution. Abstract: The variability in the amount and configuration of broad habitat types in the landscape, together with their structural complexity, influence observed biodiversity patterns. When considering structurally similar sites of the same habitat type, the variability in the abundance, species richness or diversity of organisms may be explained by the landscape context. To assess the numerical response of species to the landscape context, in terms of amount and configuration of forest environments, we investigated the bird assemblages of similarly structured forest habitats in an extensively managed forest region, encompassing different landscape contexts. We considered the numerical response of bird assemblages, in terms of abundance, species richness and diversity, and relative abundance of specific guilds, to the landscape context. We considered the forest cover at different spatial scales as a measure of habitat amount, while we quantified aspects of habitat configuration using various landscape metrics, and measured local forest structures. We found significant responses in multiple forest bird species to three important indices of forest structures: mean diameter of living trees, mean diameter of dead trees and volume of lying deadwood. Within similarly structured forest plots, bird assemblages showed responses linked with the landscape context, while plots with different habitat structure showed similar responses to the landscape context. In particular, there was a clear positive response of birds to the amount of broadleaf and mixed forest cover in the landscape. In addition, the distance between forest patches negatively affected species richness and diversity. Within landscapes, the increase of broadleaf in the existing forest area could boost abundance and diversity, decrease isolation levels for species dependent on broadleaves and enhance structural connectivity, generally favouring the majority of the species. Our findings suggest that the simple provision of habitat structures cannot represent a viable solution for biodiversity conservation and that the use of structural indicators of biodiversity like deadwood and age of canopy trees for assessing conservation value of forest needs to be integrated with landscape-scale indices. Our analysis clearly shows that the amount of habitat available in the surrounding landscape is linked with positive biodiversity responses. As human activities can alter both the provision of important habitat structures in stands across the landscape, as well as their overall landscape context, an integrated multi-scale biodiversity management is highly advisable.